متطلبات بناء القدرات والمهارات التعليمية في بيئة رقمية متغير ة - حنيش, صالح الدين (University of El-oued, 2020)
ملخص: هدفت املداخلة إلى التعرف على متطلبات بناء القدرات واملهارات التعليمية في البيئة الرقمية املتغيرة، من خالل ال طالع على مقومات البنية التحتية للبيئة الرقمية الكلية الداعمة لبناء املهارات والقدرات الالزمة في السياق التعليمي الرقمي للطالب واملعلم، وعرضت املداخلة بعض الحصائيات املقدمة من بعض الهيئات الدولية كالتحاد الدولي لالتصالت واإلسكوا وتقرير املجلس القتصادي والجتماعي حول مؤشرات التكنولوجيا الرقمية في التعليم ومؤشر املهارات في الجزائر والدول العربية، والتي أوضحت الفجوة الكبيرة للتكنولوجيات الرقمية و القدرات و املهارات في الدول العربية مقارنة بالدول املتقدمة و التي أظهرت نقطا ضعف عديدة مقارنة باملؤشرات العاملية. وخلصت املداخلة إلى أنه يجب على الجزائر وباقي الدول العربية أن تتيح املجال للكفاءات الرقمية املتخصصة لوضع رؤية بعيدة املدى يتم من خاللها النتقال من النظام التعليمي التقليدي إلى النظام الرقمي، والنظر في تكييف النظم التعليمية والتدريبية والسياسات التي تهدف إلى مواجهة تحديات البيئة الرقمية، من خالل إدراج مجموعة من املهارات الرقمية في جميع مستويات النظام التعليمي. Abstract: The intervention aimed to identify the requirements of capacity building and educational skills in the changing digital environment, by looking at the infrastructure components of the overall digital environment that support building the necessary skills and capabilities in the digital educational context of the student and teacher. The intervention presented some statistics provided by some international bodies such as the International Telecommunication Union and ESCWA and the report of the Economic and Social Council on digital technology indicators in education and the skills index in Algeria and the Arab countries. Which showed a large gap digital technologies and capabilities and skills in Arab countries compared to the developed countries, which showed twice as many dots compared to global indices. The intervention concluded that Algeria and the rest of the Arab countries must allow the specialized digital competencies to develop a long-term vision through which to move from the traditional educational system to the digital system, and consider adapting educational and training systems and policies that aim to meet the challenges of the digital environment, by including A set of digital skills at all levels of the educational system.
مقال. Ex Professo. مج5. ع.2. جامعة الوادي
Keywords: الكلمات المفتاحية : التكنولوجيا الرقمية، القدرات، المهارات، التعليم، البيئة الرقمية; key words: Digital technology, capabilities, skills, education, digital environment.